Experimental investigation of condensation of hydrocarbon refrigerants (R600a) in a horizontal smooth tube - Agra, Oezden; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
In this study, the experimental results of the condensing heat transfer coefficients of R600a, a hydrocarbon refrigerant, in a horizontal smooth copper tube with an inner diameter of 4 mm and outer diameter of 6 mm are presented at different vapor quality and different mass fluxes during condensation under annular flow conditions, by adjusting the desired vapor qualities at the test area. A specially-designed sight glass has been fitted to the inlet and outlet of the test tube to identify the flow type by naked eye after the inlet vapor quality of the refrigerant to be fed to the test area during the test is adjusted in the system. Thanks to a new method developed in the measuring system, the condensing heat transfer coefficients could be calculated by measuring the difference value (T-s-T-w) directly from the data collection unit. The experimental findings have shown that the condensing heat transfer coefficients drops down with reduction in vapor quality and the coefficient rises with the increase in the mass flux at constant vapor quality. A correlation has been developed from the data obtained. The condensing heat transfer coefficients obtained from the experimental study were seen to be consistent by +/-20% with the correlations developed by Shah, Travis and Cavallini-Zecchin. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: hydrocarbon refrigerant; condensation; heat transfer coefficients; HEAT-TRANSFER; PRESSURE-DROP; MODEL; Thermodynamics; Mechanics